Medication Abortion Experiences Before and During the COVID-19 Pandemic: A Content Analysis of Online Reddit Posts [A19]. (May 2022) - Reissner, Hana; Ponzio, Madeline R.; Nagatani-Short, Lindsay; Hurtado, Alondra; Nguyen, Brian
Abstract : INTRODUCTION: The COVID-19 pandemic impacted abortion access, prompting initiatives to improve medication abortion access. We examined self-reported experiences and inquiries about medication abortion before and during the pandemic, using the anonymous platform Reddit. METHODS: We identified medication abortion-related Reddit posts across seven subreddits (e.g., r/Askwomen, r/abortion) using keywords linked to medication abortion (e.g., "abortion pill, " "misoprostol"). We restricted our search to pre-pandemic (September-November 2019) and during pandemic (April-June 2020) and filtered posts for experiences with or questions about medication abortion. We analyzed posts via inductive and iterative coding to characterize salient themes. We examined the prevalence of themes before and during the pandemic using chi-square tests. Institutional review board approval was obtained. RESULTS: Medication abortion-related posts increased by 134% during the pandemic (70 prior vs. 164 during). Frequent themes included sharing anxieties (34%), geographic barriers (22%), privacy/secrecy surrounding abortion (21%), post-abortion relief (19%), concerns about pain/bleeding (18%), and medication seeking (12%). For posts during the pandemic, 56 (24%) mentioned COVID-19 as a barrier; more posts expressed concerns about efficacy during than prior to COVID-19 (17% vs. 3%, P <.05). We did not detect a statistically significant change in posts specifying self-managed abortion (23% vs. 27%), teleabortion (9% vs. 16%), or clinic abortion (46% vs. 32%) before versus during COVID-19. Nine posts (7%) specified interest in medication abortion above 11 weeks. CONCLUSION: Individuals share abortion experiences and seek support and advice on Reddit. Nearly a quarter of posts reported COVID-19 being a barrier to abortion access. However, concerns about abortion access, emotions surrounding abortion, and advice-seeking were prevalent across time periods.